Mobile applications to enhance self-management of gout. (October 2016) - Nguyen, Amy D.; Baysari, Melissa T.; Kannangara, Diluk R.W.; Tariq, Amina; Lau, Annie Y.S.; Westbrook, Johanna I.; Day, Richard O.
Highlights: Consumers, especially those with chronic diseases, are increasingly adopting electronic methods to manage their health. There are six applications ('apps') on the Apple and Google Play app stores available to gout patients to help them to manage their condition. Only one app incorporated all elements recommended for patient self-management of gout e.g. serum urate tracking and patient education. This app asked users to print forms to record results. Hence, no entirely electronic app is available for gout patients better manage their disease. Development of an app to support patients to self-manage their gout, and is evaluated for effectiveness at improving patient outcomes, is needed. Abstract: Background: Gout is an arthritic condition that is characterised by extremely painful, debilitating acute attacks and eventual joint and organ damage if not controlled. Despite the availability of very effective therapies that, if adhered to, will prevent acute attacks and long-term damage, the disorder is increasingly prevalent. There is an urgent need to improve self-management of gout. Objectives: Mobile health (mHealth) applications ('apps'), designed to facilitate management of chronic conditions, present novel opportunities for supporting patient self-management of gout. The aim of this review was to assess features of available gout management apps designed to assist consumers in managing their gout and their consistency with guidelines for gout management. Methods: English-language, smart-device apps designed to assist self-management of gout were identified using search term "gout" and downloaded from Apple and Google Play app stores. To be included in the review, apps had to allow users to monitor their gout disease (e.g. serum uric acid (sUA) tracking, record acute attacks) and/or educate patients about gout. Investigators derived patient-focused recommendations for gout management from contemporary guidelines. Features of reviewed apps were independently assessed by two reviewers for their facilitation of these recommendations. Results: The search identified 57 apps possibly relevant to gout management, of which six met the inclusion criteria. One app incorporated all recommendations for patient-focused gout management from guidelines including monitoring sUA, recording attacks and lifestyle advice. However, the majority of these elements were not functional within the app, and instead required users to manually complete printouts. Conclusions: Currently, only one app exists that includes all recommendations to facilitate patient self-management of gout, however some features can only be actioned manually. Given the lack of progress in achieving better patient outcomes and the promise of mHealth interventions to deliver significant gains, new or updated gout management apps are required to promote successful self-management of this chronic disease.